Emotional health cues and their influence on healthy food choice: an experimental study - Alfaqih Hidayatullah; Anna Undarwati (AcTion: Aceh Nutrition Journal, 2025)
The prevalence of obesity in Indonesia has shown a consistent upward trend, reaching 23.1%, largely driven by dietary patterns that pose health risks. Food choices are influenced not only by social and personal factors but also by environmental cues, which are the focus of this study. This research aimed to investigate the effect of affective health cues presented through human motion picture videos on individuals’ healthy food choices. A quasi-experimental design was employed in the Psychology Laboratory at Universitas Negeri Semarang in December 2024, using a simulated supermarket setting with 186 student participants selected through purposive sampling. Data were analyzed using an Independent Samples t-test. The results indicated that the human motion picture intervention significantly influenced individual food choices (p < 0.001, d = 0.98). These findings suggest that health cues play an important role in guiding individual decisions regarding healthier food options. In conclusion, environmental factors, such as health cues, can significantly impact healthy food selection and may serve as a strategic approach to reducing obesity rates in the future.